Job satisfaction and absenteeism of professionals in the Academia da Cidade Program in Brazil - Albuquerque, Amanda Emmanuelly de Melo Tavares (2020)
The aim of the study was to describe the level of satisfaction and absenteeism in the work of professionals in the Academia da Cidade Program (ACP). For this, a cross-sectional, descriptive study with a mixed approach was carried out. For data collection, a self-administered questionnaire was used for 104 professionals of the Program in Recife, Pernambuco. For the analysis of the quantitative data, the software SPSS v.10.0 was used, the results were shown in absolute and relative frequencies. Content analysis was carried out for the open questions about job satisfaction. The professionals stated that they were satisfied with the work, both from the point of view of the management of the Program (66.3%), and in a global manner (63.5%). The link with the users, the performance in health promotion and the teamwork were the aspects that most positively influenced job satisfaction and, conversely, the physical and material structure, the municipal macro management and the salary were those that contributed to the dissatisfaction of the professionals. Absenteeism due to sick leave (66.3%) was the main reason for the withdrawal of professionals from work, and the support of the worker’s health specialized team from the municipal health department was not perceived. It can be said that the professionals were satisfied with the work in the ACP, but the working conditions, the remuneration and the valorization from the management are aspects that must be improved. It is also necessary to take care of the provider, since absenteeism due to medical causes, withdrew almost half of the professionals in the period studied.